2007
DOI: 10.1093/jpepsy/jsm121
|View full text |Cite
|
Sign up to set email alerts
|

Polysomnography and Self-reported Sleep, Pain, Fatigue, and Anxiety in Children with Active and Inactive Juvenile Rheumatoid Arthritis

Abstract: Sleep was not altered in children with active JRA, however, the "first night effect" suggests that valid laboratory sleep assessments require an adaptation night.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

7
51
1

Year Published

2011
2011
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 51 publications
(59 citation statements)
references
References 25 publications
7
51
1
Order By: Relevance
“…In the present sample, 68% of children with JIA scored above the CSHQ clinical cutoff score for disordered sleep, a finding that is similar to those of previous studies (Bloom et al, 2002;Butbul Aviel et al, 2011;Ruperto et al, 2010;Ward et al, 2008). Average nighttime sleep duration was well below 8.5-10 hr the National Sleep Foundation recommends for youth.…”
Section: Discussionsupporting
confidence: 90%
See 3 more Smart Citations
“…In the present sample, 68% of children with JIA scored above the CSHQ clinical cutoff score for disordered sleep, a finding that is similar to those of previous studies (Bloom et al, 2002;Butbul Aviel et al, 2011;Ruperto et al, 2010;Ward et al, 2008). Average nighttime sleep duration was well below 8.5-10 hr the National Sleep Foundation recommends for youth.…”
Section: Discussionsupporting
confidence: 90%
“…In the few studies that have objectively measured sleep in JIA, authors have reported both sleep-disordered breathing and periodic limb movements (Passarelli et al, 2006;Ward et al, 2008Ward et al, , 2010Zamir et al, 1998). In children with chronic conditions like JIA, sleep disturbances may be a sign of an unrecognized sleep disorder that manifests as sleep fragmentation.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Evidence from a variety of patient populations and studies of healthy children suggest that children, much like adults, show improvements in sleep quality from the first to second night in the sleep laboratory, 3,[5][6][7][8][9][10]19 with some measures of sleep quality continuing to improve when data from subsequent nights are collected. 3 The most consistently reported changes are in TST, SE, WASO, and REM parameters.…”
Section: Discussion and Limitationsmentioning
confidence: 99%